Plasma proteins, cognitive decline, and 20‐year risk of dementia in the Whitehall II and Atherosclerosis Risk in Communities studies. Issue 4 (2nd August 2021) - Lindbohm, Joni V.; Mars, Nina; Walker, Keenan A.; Singh‐Manoux, Archana; Livingston, Gill; Brunner, Eric J.; Sipilä, Pyry N.; Saksela, Kalle; Ferrie, Jane E.; Lovering, Ruth C.; Williams, Stephen A.; Hingorani, Aroon D.; et al.
Abstract: Introduction: Plasma proteins affect biological processes and are common drug targets but their role in the development of Alzheimer's disease and related dementias remains unclear. We examined associations between 4953 plasma proteins and cognitive decline and risk of dementia in two cohort studies with 20‐year follow‐ups. Methods: In the Whitehall II prospective cohort study proteins were measured using SOMAscan technology. Cognitive performance was tested five times over 20 years. Linkage to electronic health records identified incident dementia. The results were replicated in the Atherosclerosis Risk in Communities (ARIC) study. Results: Fifteen non‐amyloid/non‐tau–related proteins were associated with cognitive decline and dementia, were consistently identified in both cohorts, and were not explained by known dementia risk factors. Levels of six of the proteins are modifiable by currently approved medications for other conditions. Discussion: This study identified several plasma proteins in dementia‐free people that are associated with long‐term risk of cognitive decline and dementia.